Evaluating the Effectiveness of Training Program Developed for Teachers Working with Dyslexic Students on their Competencies - KIZILKAYA, Hasan; SARI, Hakan (Asian Journal of Education and Training, 2021)
In Turkey, the number of studies determining the competence level of classroom teachers working with dyslexic students is limited. It is thought that a dyslexia training program, which will be developed based on teacher needs, will meet the training needs of teachers. In this study expletory sequential mixed method was adopted and, qualitative research method was used in the first stage and quantitative research method in the second stage. In the first stage, the teacher training program was developed in the light of the data obtained by semi-structured interview technique. Pre-test post-test control group experimental design was preferred in the process of evaluating the effectiveness of the program. The study group consists of 46 teachers working in primary schools of Karaman province. The independent samples t-test analysis between the two groups and the dependent group t-test analysis between the pre-test post-test scores revealed a significant difference between the means of the groups. As a result, teachers who consider themselves competent and receive the necessary training will both support their students with dyslexia more comprehensively and display a more positive attitude.